The pursuit of excellence : the uncommon behaviors of the world's most productive achievers - Hawk, Ryan (McGraw Hill, 2022)
"A master class in achieving and sustaining excellence-even in the most challenging times-from the host of The Learning Leader Show and author of Welcome to Management. There has never been a more challenging time to be a leader. But truly great leaders have always found a way to adapt, and even thrive, under pressure. How do they do it? Leadership expert Ryan Hawk interviewed hundreds of the most productive achievers in the world on his acclaimed podcast, The Learning Leader Show, to discover the best practices for pursuing and sustaining excellence. He found a pattern of uncommon behaviors that set these stellar individuals apart. By following their examples, you will learn how: Commit to yourself and the process-and build purpose, focus, and discipline every day Develop resilience to face new challenges-and find inspiration for the long haul Seek guidance-and lead others to new heights Meet the moment-and take every opportunity to excel Create a trusted group of advisors-and become a lifelong learner Packed with specific actions to take, experiments to run, and tools to analyze what works best for you, this uncompromisingly practical guide will inspire, challenge, support, and empower you to become your very best. Put mindsets into action and turn behaviors into habits with The Pursuit of Excellence"--